(untitled) (Research, Society and Development, 2022)
Asthma is defined as a chronic inflammatory disease, of a heterogeneous nature, very common in the pediatric age group, compromising the lower airways and presenting with intermittent episodes of wheezing, dyspnea with significant worsening during the night or in the morning, chest pain with accentuation of symptoms after exposure to allergens. The objective of the study is to evaluate the level of asthma control in patients aged 6 to 11 years old, treated between April 2021 and June 2022, at a reference Pediatric Public Hospital in Teresina-PI. This is a descriptive, cross-sectional and retrospective study, in which records of medical appointments in medical records were evaluated to analyze the level of asthma control and factors related to this control. The study was carried out with a sample of 265 medical records. All asthma guidelines suggest that asthma control should be assessed whenever possible, to verify and guide disease management and appropriate treatment, there are many measures available to assess asthma control and each of them looks at different aspects in relation to asthma. to the asthmatic patient. It is important to state that the use of more than one measure to assess asthma control will provide the health team with better information about the control and progression of the disease and, therefore, will enable better management of the treatment. It is important to note that before changing medication, the physician must assess the diagnosis, adherence to treatment and proper inhalation technique.